Evaluasi Efektivitas Program Pemeliharaan Belt Conveyor 6E1U02 Terhadap Produktivitas Unit Raw Mill PT. Semen Tonasa Menggunakan Metode Reability Centered Maintenance (RCM) - Syamsumarlin Taha; Muhammad Arham; Asnefi; Muh. Rais; Rosihan Aminuddin; Irwan Syarif; Husni Mubarak; Akhsan Hamka; Muhammad Facheruddin BJ; Jumiati Usman (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This study evaluates the effectiveness of the maintenance program aimed at identifying the causes of downtime in machines or equipment at the raw mill unit of PT. Semen Tonasa, which consists of three main sections: mechanical, electrical, and production. Based on data analysis, it was found that the causes of downtime were evenly distributed, with mechanical and production each contributing 31%, and electrical contributing 38%. The dominant cause of downtime was found in the production section, with the main issue being a broken gearbox protection. Over the past six months, the gearbox component failed twice, resulting in a total downtime of 22.30 hours. To address this issue, Reliability Centered Maintenance (RCM) was applied to identify the components responsible for machine failure. The results identified four key components contributing to downtime: the gearbox chain, Belt Conveyor, bucket elevator, and motor. The maintenance decisions taken included failure finding and time-directed life-renewal restoration for the gearbox, bucket elevator, and motor, as well as lubrication and time-directed life-renewal restoration for the Belt Conveyor chain. The expected outcome is an improvement in the reliability and performance of the machines at the raw mill unit of PT. Semen Tonasa.